Structure-stress relationships in nanocrystalline multilayered Al0.7Cr0.3N/Al0.9Cr0.1N coatings studied by cross-sectional X-ray nanodiffraction. (15th May 2019) - Klima, S.; Jäger, N.; Hruby, H.; Mitterer, C.; Keckes, J.F.; Burghammer, M.; Daniel, R.
Abstract: In this work, cross-sectional position-resolved X-ray nanodiffraction with a beam diameter of ~50 nm, was used to characterize the depth evolution of microstructure, texture and residual stress across an Al0.7 Cr0.3 N/Al0.9 Cr0.1 N multilayer coating cross-section deposited by cathodic arc evaporation. The method allowed to resolve variations in microstructure and stress state in all individual sublayers of the multilayer coating which was synthesized to include three different design approaches separated in individual sections. By this cross-sectional combinatorial approach, phase (de)stabilization in an alternating cubic and hexagonal multilayer structure (section 1), incident particle energy-dependent microstructure depth-gradients in the cubic phases (section 2) and phase (de)stabilization related to a gradual phase change from cubic to hexagonal (section 3) were investigated. While the in-plane residual stresses in the cubic AlCrN phase (sections 1 and 2) slightly fluctuated between −3 and −3.5 GPa, the compressive stress state in the hexagonal AlCrN phase showed a layer thickness dependency with values up to −6.5 GPa for sublayer thicknesses below 100 nm and down to −1 GPa for sublayer thicknesses above 600 nm. The presented results document that the cross-sectional X-ray nanodiffraction is a highly effective characterization method to investigate coatings with optimised architecture and dedicated stress design. Graphical abstract: Unlabelled Image Highlights: Development of a cross-sectional combinatorial approach based on AlCrN Highly position resolved analysis across the coating thickness Evaluation of microstructure, texture and stress gradients Control of microstructure dependent on templating effects of adjacent sublayers Control of the crystallographic structure dependent on the incident particle energy